Copywriting for the electronic media : - Meeske, Milan D. (Thomson/Wadsworth, 2005)
With this book, you will discover how to write effective copy for all types of electronic media. Nearly 80 writing assignments and examples of actual scripts, storyboards, PSAs, and promotional spots prepare you to write short, persuasive messages in a variety of venues (radio, television, new media, etc.). You'll get a glimpse of ealistic situations typical of entry-level copywriting positions along with coverage of copywriting style, consumer behavior and legal and ethical aspects of copywriting. Complete with skill-building exercises, nearly 80 writing assignments and examples of storyboards and actual aired copy, this book helps you build the understanding and skills you need for a career in this field.